2002
DOI: 10.3171/jns.2002.97.5.1203
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblastoma in the suprasellar region

Abstract: Myofibroblastoma is a rare type of benign mesenchymal tumor; only two cases of intracranial myofibroblastoma have been reported in the literature. The authors report on the case of a 34-year-old woman with a myofibroblastoma in the suprasellar region who presented with the complaint of sudden onset of headache followed within 2 weeks by progressively worsening visual disturbance. Computerized tomography scanning demonstrated a mixed low- and high-density mass in the suprasellar region and contrast-enhanced mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 20 publications
4
22
1
2
Order By: Relevance
“…The existence of a primary spindle cell sarcoma of the sella turcica in a patient who has not undergone previous radiotherapy is an extremely rare event [5]. Benign spindle cell lesions of the sellar region include meningioma, schwannoma, myofibroblastoma, solitary fibrous tumor, pituitary adenoma with spindle cell features, pilocytic astrocytoma, and pituicytoma to name a few [9][10][11]. These are readily distinguished from our obviously anaplastic tumor.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The existence of a primary spindle cell sarcoma of the sella turcica in a patient who has not undergone previous radiotherapy is an extremely rare event [5]. Benign spindle cell lesions of the sellar region include meningioma, schwannoma, myofibroblastoma, solitary fibrous tumor, pituitary adenoma with spindle cell features, pilocytic astrocytoma, and pituicytoma to name a few [9][10][11]. These are readily distinguished from our obviously anaplastic tumor.…”
Section: Discussionmentioning
confidence: 98%
“…This prompted an unsuccessful transfrontal-transventricular biopsy at another institution; the specimen was inadequate for assessment. Prior to the present surgery, blood hormone levels were normal, including growth hormone (GH) 0.02 ng/ml (<5.0 ng/ml), insulin-like growth factor 61.4 ng/ml (48-255 ng/ml), prolactin (PRL) 6.29 ng/ml (0-15 ng/ml), luteinizing hormone (LH) 2.97 mUI/ml [2][3][4][5][6][7][8][9][10][11][12], folliclestimulating hormone (FSH) 7 mUI/ml [1][2][3][4][5][6][7][8], thyrotropic hormone (TSH) 1.67 mUI/ml (0.5-6.0 mUI/ml), free T4 1.17 ng/dl (0.8-1.8 ng/dl), and cortisol 11.8 mcg/ml . Measurements of germ cell markers including human chorionic gonadotropin, alpha fetoprotein, and lactate dehydrogenase were not detected.…”
Section: Case Reportmentioning
confidence: 99%
“…To the best of our knowledge, only three cases of intracranial myofibroblastoma have previously been reported (79). The details of these case studies are summarized in Table I.…”
Section: Discussionmentioning
confidence: 99%
“…It has features of fibroblasts and smooth muscle cells, with frequent mitoses. The cells are also characterized by elongated to oval-shaped nuclei, irregular nuclear contours, finely-dispersed chromatin and poorly-defined cytoplasm (1,2,7,9,10). Immunohistochemical staining has shown that the tumor cells are strongly positive for SMA and vimentin and weakly positive for desmin and CD34 (8,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation